Virology an illustrated colour text - Korsman, Stephen N.J; van Zyl, Gert U.; Nutt, Loiuse; Andersson, Monique l.; Preiser, Wolfgang (Illustrated colour text, 2012)
This is a concise, highly accessible introduction to medical virology, incorporating essential basic principles as well as a systematic review of viruses and viral diseases. It pays particular attention to developments in anti-viral therapy that are becoming increasingly effective in modern medicine